2015
DOI: 10.21608/jpp.2015.51946
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF DIFFERENT MEDIA AND IRRIGATION AMOUNTS ON SOME GROWTH CHARACTERISTICS OF PASPALUM (Paspalum vaginatum).

Abstract: Pot expereimet was carried out during 2014-2015 On Paspalum vaginatum (paspalum turf) at research station and laboratory of the department of vegetables and ornamental plants-Faculty of Agriculture Mansoura University. Four mixtures of culture media were used to investigate the effect of compost on vegetative growth under three water levels as follows: Soil Mixtures: Media Sand% Clay% Compost% (vol./vol./vol.) 1 st medium 50 50 Zero 2 nd medium 45 45 10 3 rd medium 40 40 20 4 th medium 35 35 30 Irrigation: a.(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Salt is one of the most critical abiotic stressors that inhibit plant growth and development [33], and external morphology and growth status are the most visible indicators of the extent of salt damage to plants [34]. Salt stress has been shown to significantly inhibit the growth of the leaf length, leaf width, and leaf area of apple seedlings [35] and tropical lawns [36]. Chen et al [37] showed that high nitrate stress reduced the leaf length, leaf width, leaf area, and biomass of alfalfa.…”
Section: Growth Parametersmentioning
confidence: 99%
“…Salt is one of the most critical abiotic stressors that inhibit plant growth and development [33], and external morphology and growth status are the most visible indicators of the extent of salt damage to plants [34]. Salt stress has been shown to significantly inhibit the growth of the leaf length, leaf width, and leaf area of apple seedlings [35] and tropical lawns [36]. Chen et al [37] showed that high nitrate stress reduced the leaf length, leaf width, leaf area, and biomass of alfalfa.…”
Section: Growth Parametersmentioning
confidence: 99%